Typology of Traditional Lue tribe’s House Plan A case Study in Northern Part of Lao PDR - Anolac, Vira (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
Nowadays Lue tribe in Lao PDR settlement in flat land and lowland area along the revers or steam in each province in northern part of Lao PDR such as Luangnamtha province, Phongsaly province, Borkeo province, Luangprabang and Sayabury province. In ancient times used to belong the same group of Sipsongpanna Lue was located in the south of China, afterward they moved to Northern part of Lao PDR. This paper is a part of the research project, the transformation of traditional Lue tribe house in Lao PDR, focus study in the general for summary basic information such as house plan, culture, traditional and believe for studying and create an initial knowledge of Lue tribe in Lao PDR. The results of study found the typologies house plan of Lue tribe classified in two types as the following: 1. Typology of traditional Lue tribe house which has pillar male (Sao Thao) located in the East of the house and pillar female (Sao Nang) located in the West of the house, popular built this house in the group of Luekalom, 2. Typology of traditional Lue tribe house which has pillar male (Sao Thao) located in the West of the house and pillar female (Sao Nang) located in the East of the house, popular built this house in the group of Lue.